Primary Failure of Eruption (PFE) – case reports - Chodorowska-Cymbor, Katarzyna; Kaczyńska , Joanna; Szarmach, Izabela J. (Journal of Stomatology, 2015)
Introduction. Primary Failure of Eruption (PFE) is a very rare disease, which may be defined as an isolated eruption disorder of non-ankylosed teeth in the absence of mechanical obstacles. Aim. To present cases diagnosed with Primary Failure of Eruption. Material and methods. Patients admitted to the Department of Orthodontics for consultation and treatment were interviewed. The clinical analysis and radiological diagnostics were performed. Extraoral and intraoral photographs were taken, the plaster casts were prepared. Based on the results, the first patient was diagnosed with unilateral PFE involving teeth 36, 37, 38 in the right mandible. In the second case, PFE type II was identified on teeth 16, 17. The third patient was diagnosed with PFE type I bilaterally in the maxilla, concerning teeth 17, 18, 27, 28. The treatment plan was adapted individually to each case. Conclusion. Patients diagnosed with PFE require multidisciplinary therapy, including surgical and prosthetic treatment, without the application of orthodontic force.